The Role of Colonialism in Britain’s Wealth Accumulation: Examining Wealth Drain and Exploitation of India and Hong Kong - Liu, Rui (International Journal of Social Sciences and Public Administration, 2025)
This essay examines the role of colonialism in Britain’s wealth accumulation, focusing on the exploitation of India and Hong Kong during the British Imperial era. It argues that Britain’s status as a first-world country with the world’s fifth largest economy is significantly due to the economic gains from its colonial past. The paper details the "Drain" of wealth from India, where Britain extracted nearly 45 trillion from 1765 to 1938, and the subsequent deindustrialization of India’s economy. It also discusses the cost of conquering, land revenue systems, and the shared military burden that India bore, which alleviated Britain’s financial strain during wars. The social benefits provided by Britain in India, such as railways, were financed by Indian taxpayers, with British investors reaping the profits. Turning to Hong Kong, the essay highlights the opium trade as a state-run business that funnelled profits to Britain and the transformation of Hong Kong into a trade and foreign investment hub, with real estate becoming a significant contributor to its GDP. The colonial government’s policies in Hong Kong resulted in low tax revenues for the colony, yet high profits for British companies. The essay concludes that Britain’s wealth and the strategic trade opportunities in its former colonies were made possible through imperialism, leaving a legacy of socio-economic imbalance and exploitation.